IAPSM’s Position Paper on Typhoid Vaccines for Adult Immunization in India - Kapil Goel; Madhur Verma; Nikita Sharma; Swayam Pragyan Parida; Anu Bhardwaj; Anuradha Nadda; Sahil Sharma; Arunima Sen; Jacob John; Adarsh Bansal; Madhu Gupta (Indian Journal of Community Medicine)
Typhoid is a major public health concern in India, particularly among those dwelling in urban slums with poor sanitation. The disease caused by Salmonella enterica serovar Typhi spread majorly through contaminated food and water. The economic burden of the disease is catastrophic and affects both families and the government making a strong case for including typhoid vaccines in the national immunization schedule. The World Health Organization has prequalified several vaccines and has recommended their use in endemic areas. While there is robust evidence for vaccination of children from India and other LMICs, the case for adult vaccination remains less clear. The Indian Association of Preventive and Social Medicine acknowledges the necessity to adopt a widespread typhoid immunization program, along with other preventive strategies, especially in the vulnerable pockets. IAPSM recommends focusing on newer-generation Typhoid Conjugate Vaccines (TCVs), which provide long-lasting and superior immunological benefits, and are effective across all ages including adults. IAPSM suggests routine use of Typbar-TCV™ for adults up to 45 years old in India. The organization also highlights the necessity for post-marketing surveillance of these vaccines, to monitor the long-term safety and effectiveness of various vaccines in different communities. IAPSM encourages members to take front-line efforts in their community health service areas, and finally appeals for the development of vaccines to cover a more extensive range of Salmonella infections so that control over typhoid can be strengthened.